The existence of adrenal insufficiency in patients with COVID-19 pneumonia - Porntharukchareon, Thachanun; Dechates, Bothamai; Sirisreetreerux, Supamas; Therawit, Phonthip; Tawinprai, Kriangkrai (Frontiers in Endocrinology, 2024)
Introduction: Infection with SARS-CoV-2 virus may result in long COVID, a syndrome characterized by symptoms such as dyspnea, cardiac abnormalities, cognitive impairment, and fatigue. One potential explanation for these symptoms is hypocortisolism . Objective: To evaluate the prevalence of hypocortisolism in patients with a history of COVID-19 pneumonia. Methods: Cross-sectional study of patients who were aged ≥18 years and had a 3-month history of radiography-confirmed COVID-19 pneumonia. Exclusion criteria included current or previous treatment with glucocorticoids and use of an oral contraceptive. Adrenal function was evaluated using a low dose (1ug) corticotropin stimulation test (CST). Serum cortisol levels were measured at 0, 30, and 60 minutes, and baseline plasma ACTH was also measured. Results: Of the 41 patients enrolled, the median age was 62 years, 17 (42%) were female, and all 41 (100%) had severe pneumonia at baseline. Eleven patients (27%) had hypocortisolism, as evidenced by peak cortisol of less than 402.81 nmol/l after low dose (1 µg) CST. Of these 11 patients, 10 (91%) had secondary hypocortisolism (median ACTH 6.27 pmol/L, range 4.98–9.95 pmol/L) and one had primary hypocortisolism (mean ACTH 32.78 pmol/L). Six of the 11 patients with hypocortisolism (54.5%) reported symptoms of persistent fatigue and 5 (45.5%) required regular glucocorticoid replacement. Conclusions: Our results suggest that hypocortisolism, predominantly caused by pituitary disruption, may emerge after SARS-CoV-2 infection and should be considered in patients with a history of COVID-19 pneumonia with or without clinical hypocortisolism.